Closure time of ductus arteriosus after birth based on survival analysis. (June 2018) - Iwashima, Satoru; Satake, Eichirou; Uchiyama, Hiroki; Seki, Keigo; Ishikawa, Takamichi
Abstract: Objectives: The correct ductus arteriosus (DA) closure time is somewhere between the opening and closing time confirmed on echo, not on examination. We investigated DA closure time and factors affecting DA closure time using interval censoring analysis. Methods: This was an observational, retrospective study including 2611 healthy neonates. Echo was performed every 12–24 h after birth until DA closure. We investigated the DA closure time using interval censoring analysis. If the DA was closed on echo, we assumed that the DA was open at birth. We evaluated clinical factors affecting DA closure time. Results: Median DA closure time was 13.5 h (range, 7.7–18.7 h) after birth. DA closure time was associated with primipara status, maternal prostaglandin E2 (PGE2) administration, <2500 g birth weight, and diagnosis of congenital ductus arteriosus aneurysm (DAA). Using proportional hazards regression models, the interval-censored data (primipara, hazard ratio [HR] = 1.099, P = 0.04; PGE2, HR = 0.823, P = 0.03; <2500 g, HR = 1.413, P < 0.01; DAA, HR = 0.570, P < 0.01) were found to be significantly associated with DA closure time. Conclusions: Estimation of DA closure time by interval censoring analysis is helpful to determine the optimal time to perform echo and to predict risk factors for patent DA. Highlights: In healthy neonates, the DA closes within 3 days of birth, based on echocardiography. However, the correct ductus arteriosus (DA) closure time is somewhere between the opening and closing time confirmed on echo, not on examination. We investigated DA closure time and factors affecting DA closure time using interval censoring analysis. The median DA closure time was 13.5h (7.7-18.7 h) after birth.